Pengaruh Intensitas Penggunaan Whatsapp Group Terhadap Kedekatan Sosial Generasi-Z Di Kota Surakarta - Aurelia Retno Wulan; Clarinsa Hanin Hermawan; Ismail (CV. Multi Kreasi Media, 2025)
The development of digital technology has changed social communication patterns, especially among Generation Z, who have grown up as digital natives. One of the most dominant means of communication is WhatsApp Group, which enables fast, massive, and continuous interaction. This study aims to determine the effect of the intensity of WhatsApp Group usage on the social closeness of Generation Z in Surakarta City. The study uses a quantitative approach with a positivistic paradigm. Data were collected through a Likert scale-based questionnaire distributed online to 100 Generation Z respondents who actively use WhatsApp Groups, using purposive sampling techniques. The independent variable in this study is the intensity of WhatsApp Group usage, measured through indicators of attention, duration, frequency, and immersion, while the dependent variable is social closeness, measured using the stages of social penetration theory. Data analysis was conducted using normality tests, linearity tests, Pearson's correlation, and simple linear regression. The research results are expected to show a positive and significant influence between the intensity of WhatsApp Group usage and the social closeness of Generation Z. This study provides theoretical contributions to the study of digital communication as well as practical benefits for understanding the social interaction patterns of the younger generation in the digital era.